Refleksi Konsep Sufistik Perempuan: Tinjauan terhadap Naskah Raden Dewi Murtasiya - Erro Witjaya Kusuma; Hanafi (Manuskripta, 2025)
Sufi figures serve as inspirational narratives capable of shaping the social construct of Sufic dynamics studied by women. The representation of Raden Murtasiya as a spiritual figure in ancient Javanese manuscripts provides profound insights into understanding domestic family relationships through a Sufi perspective. This study aims to examine the reflection of Raden Murtasiya as a symbol of female Sufism within the Raden Murtasiya manuscript. The Sufi teachings in this text practice the values of asceticism (zuhd), patience (sabr), and sincerity (ikhlas) as the foundation for bridging Sufic principles with the domestic sphere. Using a philological approach, the methodology encompasses manuscript inventory, description, transliteration, and translation. This research utilizes a comparative study between the Raden Murtasiya manuscript from the British Library (Endangered Archives Programme) and the collection of the Sonobudyo Museum as documented in Fajar Wijanarko’s work. The findings indicate that Raden Murtasiya exemplifies an expressive and active form of Sufism. The Sufic values within this manuscript foster spiritual consciousness through Raden Murtasiya's journey. === Tokoh sufi menjadi kisah inspiratif yang mampu memberikan konstruk sosial terhadap dinamika tasawuf yang dipelajari oleh perempuan. Representasi Raden Murtasiya sebagai tokoh spritual pada naskah kuno Jawa, memberikan pemahaman dalam memahami hubungan domestik keluarga perspektif tasawuf. Penelitian ini bertujuan untuk melihat refleksi Raden Murtasiya sebagai simbol sufi perempuan pada naskah Raden Murtasiya.  Ajaran tasawuf pada pada naskah Raden Murtasiya mengamalkann nilai-nilai kezuhudan, sabar, kemudian ikhlas sebagai dasar ajaran antara nilai tasawuf dengan ranah hubungan rumah tangga. Metode dalam penelitian ini menggunakan pendekatan filologi dimulai dari Inventarisasi naskah, deskripsi naskah, transliterasi, dan terjemahan. Perbandingan naskah yang digunakan ialah naskah Raden Murtasiya koleksi the British Library (Endangered Archive Programme) dan koleksi Museum Sonobudyo dari buku Karya Fajar Wijanarko. Hasil penelitian ini menunjukkan Raden Murtasiya menunjukkan ajaran tasawuf yang ekspresif dan aktif. Nilai-nilai sufistik pada naskah ini dapat membentuk kesadaran spritual melalui perjalanan Raden Murtasiya.